Veto power and power-sharing: insights from Burundi (2000–2018). Issue 7 (3rd October 2019) - McCulloch, Allison; Vandeginste, Stef
ABSTRACT: Veto power is a key institutional pillar of consociational power-sharing. However, the literature is divided on its impact for institutional functionality. While the founding father of consociational theory, Arend Lijphart, expects veto rights to be exercised sparingly by segmental elites, more recent scholarship emphasizes the need for restrictions (in terms of veto players, veto issues, veto points and procedure) in order to avoid abusive and disruptive veto practice. Burundi's transition from ethnic conflict to ethnic pacification was strongly based on the use of military and political power-sharing, including consociationalism. This article examines the design of veto rights and their practice in Burundi over the past two decades. The analysis confirms that the institutional design of veto power matters, but it counters the hypothesis that a too enabling veto design induces the abuse of veto rights and disrupts consociational functionality. The Burundi case-study shows that the impact and "shelf-life" of veto rights are best understood by taking into consideration the intersection of veto power with other power-sharing institutions and practices, both formal and informal.